2014
DOI: 10.1002/jbio.201400005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of geometry on tumor thermal profile and its use in tumor functional state estimation

Abstract: Thermal differences between transplanted tumors and tumors in humans prevent the implementation of thermographic methods developed in mice models to human models and vise-versa. Transplantable tumors tend to have an extruding shape, which may affect the thermal patterns. This hypothesis was studied in phantom experiments and simulations. A correlation between tumor dimensions and relative temperature was found and used to estimate tumor functional state from previously published in vivo experiments. A correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…It should also be noted that the calculated values of ΔT functional are low when compared to the previous research. This may be due to different settings in this experiment when compared to Tepper et al, 31 and should be explored to reduce possible errors. At the final stages of the experiment, wounds were formed on the tumor surface.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It should also be noted that the calculated values of ΔT functional are low when compared to the previous research. This may be due to different settings in this experiment when compared to Tepper et al, 31 and should be explored to reduce possible errors. At the final stages of the experiment, wounds were formed on the tumor surface.…”
Section: Discussionmentioning
confidence: 97%
“…However, as shown in previous studies, the tumor temperature in animal model studies shows a different dependence on tumor volume, when compared to human model studies. 31 The tumors are cooler than their surrounding tissues and this temperature difference may increase as the tumor grows. A possible explanation for these observations was proposed and is supported by both phantom experiments and simulations: tumors in animal models are often transplanted, leading to increased tumor growth rates when compared to spontaneously occurring human tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was previously speculated to be a result of poorly organized and hyperpermeable blood vessels [21]. However, it has been shown that another possible reason may be the extruding shape of the lump that causes the thermal cooling, due to enhanced radiation and convection from the tumor surface area [23].…”
Section: Introductionmentioning
confidence: 99%